The Effect of Storage Time on the Total Lactic Acid Bacteria and Presence of Gram Positive and Negative Bacteria in Calf Starter Pellet Added with Fermented Cabbage Waste - Sri Mukodiningsih; Retno Iswarin Pujaningsih; Resniati Resniati; Andriyani Astuti (Buletin Peternakan, 2019)
The aim of this research was to examine the microbiological quality of calf starter pellet added with fermented cabbage waste after stored for 0, 4, and 6 weeks. The materials used in this research consisted of cornmeal, rice bran, soybean meal, molasses, mineral mix, and fermented cabbage waste. This research used Completely Randomized Design with 4 treatments and 3 replications. The mixed calf starter pellet consisted of 100% calf starter and 6% of fermented cabbage waste, and then stored for 0 weeks (P0), 2 weeks (P1), 4 weeks (P2) and 6 weeks (P3). The observed microbial qualities were the total lactic acid bacteria and the presence of gram positive and negative bacteria in the mixed calf starters. The total lactic acid bacteria were analyzed descriptively, while the presence of gram bacteria was analyzed with analysis of variance followed with Duncan’s test. The result of this research showed that an increase in storage time would result in lower lactic acid bacteria population, while the gram-positive and negative bacteria was not significantly affected. The research concluded that 6-weeks stored calf starter pellet added with 6% of fermented cabbage waste could maintain its lactic acid and gram-positive bacteria population, while also reducing its gram-negative bacteria population as well.